O YouTube e as identidades presentes no canal Small Advantages: uma análise multimodal a partir da Semiótica Social - Regina Celia Lopes Brito (2021)
Taking the environment of the YouTube sharing platform, this work proposes to investigate and analyze the identities presented by the so-called "influencers" and by their "followers", through non-verbal semiotic modes. In order to study these subjects and the identities projected by them, we chose as a Corpus of Analysis a YouTube channel well known to the public, mainly in Brazil: Small Advantages, by Gavin Roy. Based on Social Semiotics (HODGE; KRESS, 1988; VAN LEEUWEN, 2005; KRESS, 2010) and from the perspective of multimodality (KRESS; VAN LEEUWEN, 2001; KRESS, 2010), we began our research by listing six categories: a) appearance of youtuber; b) scenery and setting; c) camera and editing; d) use of colors; e) typography used and f) voices, sounds and music. For the analysis, we used the Grammar of Visual Design (KRESS; VAN LEEUWEN, 2006, 2021), the Semiotics of Sound (VAN LEEUWEN, 1999 and 2012), the Semiotics of Light (VAN LEEUWEN AND BOERIIS, 2017), the Theory of Kineikonic Metamodes (BURN, 2013), studies on Typography (KRESS; VAN LEEUWEN, 2010 and VAN LEEUWEN, 2006), and studies on Colors (KRESS; VAN LEEUWEN, 2002). During this research, we also introduced the concept of Text-Environment, which is characterized by being the orchestration of all semiotic modes in a given physical space, thus causing sensations, evoking memories and feelings in those who are able to interpret it. From the analyzes carried out, we found that, over the years of the channel's existence, between 2015 and 2019, there was a drastic change in the appearance of the youtuber. The difference between the amateur and the professional youtuber can be seen clearly, whether in the personal appearance, in the use of colors, or even in the typography used in the videos. If, at first, there was not so much preparation, visually, for making the videos, we could see after our analysis that there has been a big change since then. However, all these changes were made, basically, to demarcate or reaffirm the identity of the youtuber as being someone simple and accessible. With regard to his following audience (the smallists), at the beginning of the channel, he is placed as a friend, someone who can be counted on to learn and teach something, and who, therefore, has a great degree of approximation with Gavin. As time went by and through the transformation of the channel and Gavin himself, his following audience was also gradually changing. If there was curiosity, and even a certain amount of admiration, to see a foreigner become interested in the language and culture of Brazil, now the main interest is to get some English tips or to see the youtuber in his trips in Brazil. Social Networking Sites are a vast portrait of the history of humanity in the 21st century. Ultimately, we consider the importance of studying this theme, mainly due to the lack of research that takes into account the non-verbal semiotic modes present in interactions mediated by the YouTube platform.